Factors contributed to the occurrence of peptic ulcer disease in patients at Champasack Provincial Hospital, Pakse, Laos - Phomphithak , Chansy; Luangsombath , Soulichanh; Phothiladth, Ammalin (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objectives of this study was to compare the personal factor between the PUD group and the Non-PUD group contributing to occurrence of the peptic ulcer, to compare the interpersonal factor between the group of PUD and Non-PUD group resulting in the occurrence of the peptic ulcer, to compare social-culture factors and law between the PUD group and the non-PUD group leading to the occurrence of peptic ulcer. The method applied was an analytical study using Case-control study to determine factors resulting in the occurrence of peptic ulcers of patients at Champasak Hospital, Lao PDR. The study took place between January 2019 and May 2019. The sample group comprised of 96 patients whose age was over 18. Researchers categorized sample group into 2 groups: PUD (Case) comprised of 48 patients and non-PUD (Control) included 48 patients. Data were collected using medical records and an ecological risk questionnaire form. Data were analyzed using descriptive statistics to find the frequency, average, percentage, and standard deviation χ 2. The analysis used simple logistic regression and multiple logistic regression. The study groups with H. pylori infection were (M=4.88) more likely to develop a peptic ulcer than those without H. pylori infection. Non-steroidal anti-inflammatory drugs were more prone to peptic ulcers than non-steroidal anti-inflammatory drugs 107.81. Alcoholic drinking groups were (M=31.61) more at risk than those without alcoholics. Having food incorrect time, (M=45.22) more likely to develop a peptic ulcer than the group eating food on time. Multivariate analysis of factors related to the occurrence of peptic ulcers showed that those who had close friends were more likely to drink alcohol at (M=7.37) more risk than those who did not accepted and those whose families do not have alcohol prohibitions are at greater risk of developing ulcers than those whose families have a prohibition on drinking (M=3.98). Multivariate analysis of factors related to the occurrence of peptic ulcers found that those who bought alcohol after 16.01 hrs were more at risk of peptic ulcer than those who bought alcohol at 08.00-16.00 hrs. (M=5.02).